Globalisation and Methodology of Researches in International Trade - Stanojevic, Natasa; Kotlica, Slobodan (Industrija, 2018)
The intensive globalization of production at the end of the 20th and the beginning of the 21st century led to a significant distortion of statistical data of the volume of international trade. The usage of these data in quantitative research does not provide reliable information regarding the development potential of a particular export route (orientation) or products. The specific methodological procedure has been proposed in order to correct these data, prior to their application in known econometric models. It includes standard procedures for separation of inter-industry from intra-industry trade, and then the differentiation of horizontal and vertical form of intra-industry exchange. In the last step, the disputed value of exports is identified by marking unusual situation of higher export price of undeveloped economies to the developed ones. This is a result of the multiple crossing of the border of the same products. The obtained corrected value of statistical data can be successfully applied in existing econometric models. The methodological procedure was applied to the selected Serbian export groups of products and several of its key export partner countries. The results show that th